Study Of Techno-Economic Aspects In Small Industries Producing High Acid Cpo Capacity 2 Tones Per Day - Yazid Ismi Intara; Arif Budiman Budiman; Hidayat Koto (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: this study aims to analyze the business sensitivity of a factory producing high acid crude palm oil (HACPO) in Pasar Bembah Village, Air Napal District, North Bengkulu Regency, and to study a factory in the form of a small-scale palm oil industry that processes palm oil pulp into non-food CPO. The technical and financial aspects of the business will also be considered. Metodology: the procedure carried out was collected technical and financial information on the small factory of High Acid CPO from the financial perspective (NPV, IRR, and Payback Period) to assess the feasibility of the business. Sensitivity analysis was carried out by considering conditions which vulnerable to change, and as final assessement the practicality of the business. Result: results of the study from the technical and financial aspects show that the Mini High Acid CPO Factory with a capacity of 2 tons per day in Pasar Bembah Village, Air Napal District, North Bengkulu was feasible executed. Feasibility because it can be supported by the availability of raw materials, labor costs, production processes, machinery and equipment, production capacity, and environmental impacts. The results of the business sensitivity analysis showed that the decline in selling prices and spikes in raw material costs have an impact on the HACPO Business. Originality: study examines about just started to develop bussines of the techno-economics of small factory HACPO for non-food CPO products. Type of research: explained descriptive quantitative research in techno-economic prespective of small business HACPO.